Lived Experience from the Inside Out : Social and Political Philosophy in Edith Stein - Calcagno, Antonio, 1969- (Book collections on Project MUSE., 2014)
"Focusing on significant texts from Edith Stein's early philosophical work, this book explicates rich sources of social and political insight, with Stein's particular focus on individual consciousness as the entry point: how we understand and live, always from our own interiorities, the phenomenal experiences of self, others, the masses, society, community, and the state"--